2004
DOI: 10.1242/dev.01318
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signals across the plasma membrane to activate the β-catenin pathway by forming oligomers containing its receptors, Frizzled and LRP

Abstract: Wnt-induced signaling via beta-catenin plays crucial roles in animal development and tumorigenesis. Both a seven-transmembrane protein in the Frizzled family and a single transmembrane protein in the LRP family (LDL-receptor-related protein 5/6 or Arrow) are essential for efficiently transducing a signal from Wnt, an extracellular ligand, to an intracellular pathway that stabilizes beta-catenin by interfering with its rate of destruction. However, the molecular mechanism by which these two types of membrane re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
315
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(339 citation statements)
references
References 54 publications
(97 reference statements)
22
315
2
Order By: Relevance
“…Moreover, at least in certain overexpression assays, LRP5/6 can activate the canonical Wnt pathway independently of Frizzled and Dishevelled (Mao et al, 2001;Cong et al, 2004a, b). While normal Wnt signaling requires Frizzled, LRP6 and Dishevelled (Mao et al, 2001;Schweizer and Varmus, 2003;Cong et al, 2004b), the overexpression assays show that LRP5/6 can function without Frizzled or Dishevelled. So what is phosphorylated LRP5/6 doing?…”
Section: How Does Dishevelled Affect the Destruction Complex?mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, at least in certain overexpression assays, LRP5/6 can activate the canonical Wnt pathway independently of Frizzled and Dishevelled (Mao et al, 2001;Cong et al, 2004a, b). While normal Wnt signaling requires Frizzled, LRP6 and Dishevelled (Mao et al, 2001;Schweizer and Varmus, 2003;Cong et al, 2004b), the overexpression assays show that LRP5/6 can function without Frizzled or Dishevelled. So what is phosphorylated LRP5/6 doing?…”
Section: How Does Dishevelled Affect the Destruction Complex?mentioning
confidence: 99%
“…One suggestion is that the binding of Dishevelled to Frizzled recruits Dishevelled to the membrane where it activates the Wnt co-receptor Lipoprotein receptor-related protein 5/6 (LRP5/6) using the Dishevelled-binding protein CK1e (Dale, 2006). Alternatively, or in addition, it has been suggested that the Wnt-dependent translocation of Dishevelled to the membrane is involved in recruiting Axin to the membrane since Dishevelled binds Axin through its DIX domain (Kishida et al, 1999;Li et al, 1999) and thus Dishevelled could tether Axin to Frizzled, which together with LRP5/6, inactivate the destruction b-Catenin destruction complex D Kimelman and W Xu complex (Cliffe et al, 2003;Schweizer and Varmus, 2003;Cong et al, 2004b). However, Dishevelled lacking its PDZ domain can still activate the Wnt pathway in at least some overexpression experiments (note that not all experiments produce this conclusion, but this may be due to the fact that some authors delete only a minimal PDZ domain whereas other authors delete adjacent sequences that might be essential Axelrod et al, 1998;Rothbacher et al, 2000;Cong et al, 2004a).…”
Section: How Does Dishevelled Affect the Destruction Complex?mentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Low-density lipoprotein (LDL) receptor-related proteins 5 and 6 (LRP5/6), members of the low-density lipoprotein receptor (LDLR) family, are single-pass co-receptors that interact directly, albeit poorly, with Wnts, and form a Wnt-induced ternary complex with Fz that mediates b-catenin signaling. (2,(5)(6)(7)(8) LRP5/6 have an overall homology of 71%. (9) They are essential for Wnt/bcatenin signaling and are part of the LDL receptor family with a number of distinct conserved motifs, including complement-like cysteine-rich repeat motif (the LDL repeat), epidermal growth factor (EGF) receptor-like repeats, tyrosine-tryptophan-threonine-aspartate (YWTD) repeats that form a b-propeller structure critical for proper ligand binding, and proline-proline-prolineserine-proline (PPPSP) motifs that are phosphorylated and important for downstream pathway activation.…”
Section: Introductionmentioning
confidence: 99%